Smart Ways to Manage Waste with AI and IOT: A Review - Yash Sharma; Ranveer Chaudhary; Dr. Stuti Saxena (International Journal of Advanced Control and System Engineering, 2025)
Rapid urban growth and population have led to exponential growth in municipal solid waste over traditional inefficient waste management systems (collection / segregation / disposal). This paper reviews the convergence of Internet-of- Things (IoT) and artificial intelligence (AI), seen as two potential smart techniques to launch smarter waste management. The research reports important applications for AI and IoT in waste classification, waste collection optimization, waste-to-energy as well as smart bin monitoring by referencing the surrogate of recent literature. The review discusses the advantages of these techs such as enhanced eco-friendly status and conditions, real-time tracking, impact in cost and time. Nevertheless, there are still problems remaining including high infrastructure cost, data integrity, and adoption barriers for low- and middle-income countries. The work points to the neglected areas of industrial as well as e-waste and suggests more comprehensive research in a variety of socioeconomic settings with establishment of hybrid AI models. The objective of the study is to inform future efforts at designing smart sustainable scalable systems for management of garbage.
Keywords: Artificial Intelligence (AI); Internet of things (IoT); Smart waste management; Sustainable urban development; Waste Collection Optimization